Litterfall and restitution of nutrientes in secondary forests of the coast Paraná state - Woiciechowski, Thiago; Marques, Renato (Revista Ecologia e Nutrição Florestal - ENFLO, 2017)
Monthly collections of litterfall were collected in secondary forest areas with different ages under the control of Dense Ombrophylous Submontane Forest in Paraná state 25 collectors of 1 m² suspended systematically distributed in 1 ha each; with the objective of estimating the production of litter: Annual, seasonal, by fractions leaves, twigs, reproductive organs and remains, and the amount of nutrients restored. Secondary forests were called SF, with SF-1 and SF-2 being approximately 100 years old (more developed); SF-3 and FS-4 between 60 and 80 years (intermediate); SF-5 between 40 and 60 years and SF-6 between 20 and 30 years (less developed). After the quantifications of the phytomass, homogenization and milling were performed for chemical analyzes of C, N, P, K, Ca and Mg. The annual production was between 5 and 10 Mg ha-1 year-1 and a statistical difference was observed in annual and seasonal production, with summer and spring being the highest deposition rates. The annual deposition had no relation with the age and phytosociological structures of the forests.The leaves fraction was responsible for the higher rates and pattern of deposition in the areas, but the miscellaneous fraction contributed to the higher nutrient return in the soil in the more developed forests. The annual amount of nutrients returned had the sequence C>N>Ca>K>Mg>P in the areas, with the exception of FS-1, with a higher content of Mg in relation to K. The sequence in the annual nutrient supply was FS- 1 = FS-2>FS-5>FS-6>FS-4>FS-3 concluding that more developed forests returned more nutrients to the soil.